Effects of Immobilization Devices on Skin Doses and Doses in the Build-Up Regions for High Energy Photon Beams - Djan, B. (University of Ghana, 2018)
This study presents the significant increase in skin dose caused by the presence of thermoplastic immobilizing masks used for positioning and immobilization of patients during cancer treatments in the head and neck region. Made from organic materials, thermoplastics become soft and pliable when heated and forms a rigid replication of the patient’s anatomy as it cools down. The use of the mask plays a key role in achieving the therapeutic aim in head and neck treatments but can as well lead to a rise in surface dose. The purpose of this research is to examine and analyze the effects of thermoplastic masks used as immobilization devices on skin and the build-up region doses for a 6 MV Three Dimensional Conformal Radiotherapy plan. Measurements in the solid water phantom coupled with an electrometer and a Roos type ionization chamber at the surface (skin), the dmax (1.6 cm) and a specified depth of 10 cm of the 6 MV photon beam were made and recorded employing the isocentric technique for known varying field sizes with 100 MU. Measurements with or without the mask were also made on the phantom. GafChromic films were also used to assess the skin dose and dmax and compared to the measured values. Surface dose increased significantly due to the presence of the thermoplastic masks. It was observed that the estimated surface doses with the presence of the thermoplastic mask were consistently larger than those without the mask. Due to the presence of the thermoplastic mask during measurements, the dose in the build-up region increased, subsequently shifting the depth of maximum dose, dmax, to shallower depths to the skin surface. For a field size of 10 x 10 cm2, an increase in skin dose of 0.21, 0.13 and 0.05 Gy was estimated for the unstretched mask, the 5 cm stretched mask and the 10 cm stretched mask respectively, which was ascribed to the “bolus” effect of the thermoplastic masks. For the various field sizes, the skin dose increased by an average factor less than 1% for the different mask stretches. However, a variation within 1% was recorded although the skin dose decreased as the mask was extended. The thermoplastic factor at the skin surface was also found to increase with an increasing mask thickness and for a particular mask type (unstretched, 5 cm stretched, or 10 cm stretched) the thermoplastic factor decreased with increasing field size. The discrepancies obtained using the GafChromic films varied significantly with those obtained using the ionization chamber which was associated with the heterogeneous composition of the film arising from the manufacturing process. The skin-sparing effect which is an advantage for megavoltage beams was not achieved due to the presence of the masks.
Thesis (MPhil)
Keywords: Radiotherapy; Dimensional; Immobilization; Thermoplastic; Heterogeneous